PSYCHOLOGICAL FACTORS IN THE MANIFESTATION OF PROCRASTINATION AMONG STUDENTS - Yuldasheva Nilufar Sherqo’zi qizi; Karimova Madina Ma’rufdjanovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Procrastination, the voluntary delay of intended actions despite foreseeable negative consequences, is a prevalent issue among students. This article explores the key psychological factors contributing to the manifestation of procrastination in academic settings. Drawing upon recent research, it examines the roles of motivation, self-regulation, fear of failure, perfectionism, time management skills, and underlying psychological conditions such as anxiety and depression in fostering procrastination behaviors. Understanding these factors is crucial for developing effective intervention strategies to support students in overcoming procrastination and enhancing their academic performance and well-being.